Obrazy stworzenia świata w poezji Jana Pawła II i ks. Janusza S. Pasierba = Creation of the world in the poetry of John Paul II and fr. Janusz S. Pasierb - Peroń, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The poetry of John Paul II and fr. Janusz S. Pasierb refers to the biblical description of the creation of the world. Inspiration is drawn from art as well as autobiographical facts from the poets` lives. John Paul II in the "Roman Triptych" describes the meeting of God and man and recalls the frescoes by Michelangelo in the Sistine Chapel. Fr. Pasierb`s poetic cycle "Genesis" describes medieval statues of Chartres cathedral. While Pasierb asks abort the meaningfulness of the creative act which is associated with the departure of man and with God`s suffering, John Paul II expresses his admiration and amazement over the power of the Creator.
Keywords: Jan Paweł II, papież (1929-2005); Pasierb, Janusz (1929-1993); poezja polska - 20 w.; poezja religijna